2016
DOI: 10.1063/1.4948291
|View full text |Cite
|
Sign up to set email alerts
|

A broadband toolbox for scanning microwave microscopy transmission measurements

Abstract: In this paper, we present in detail the design, both electromagnetic and mechanical, the fabrication, and the test of the first prototype of a Scanning Microwave Microscope (SMM) suitable for a two-port transmission measurement, recording, and processing the high frequency transmission scattering parameter S21 passing through the investigated sample. The S21 toolbox is composed by a microwave emitter, placed below the sample, which excites an electromagnetic wave passing through the sample under test, and is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Scanning microwave microscopy has developed into a very broad research topic since its introduction and is favored by many researchers due to the nondestructive advantages of microwave testing [57][58][59]. It has now been successfully applied to characterize surface and subsurface samples at the nanoscale spatial resolution, exploring properties such as dielectric constant, doping concentration, and resistivity.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Scanning microwave microscopy has developed into a very broad research topic since its introduction and is favored by many researchers due to the nondestructive advantages of microwave testing [57][58][59]. It has now been successfully applied to characterize surface and subsurface samples at the nanoscale spatial resolution, exploring properties such as dielectric constant, doping concentration, and resistivity.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…62, the authors presented a rigorous modeling of nanosized SMM probes and their electrodynamic interaction with material samples at microwave frequencies [62]. They concluded that the SMM had the potential for use as a broadband dielectric spectroscopy operating at higher frequencies up to THz [63,64]. The numerical simulation is carried out by the finite element method (FEM).…”
Section: Quantitative Measurements Of Nanoscale Permittivity and Condmentioning
confidence: 99%
“…This feature is particularly vital for conducting microwave characteristic testing in the fields of semiconductor devices and materials. [22][23][24] As a result, our research focuses on probe fabrication, microwave frequency tests, and imaging techniques to discern their potential applications in SMM testing technology.…”
Section: Introductionmentioning
confidence: 99%